Cytomegalovirus in donors for fecal microbiota transplantation, the phantom menace? - Tatiana Galpérine; Ilka Engelmann; Sebastien Hantz; Déborah Postil; Anny Dewilde; Dominique Deplanque; Renaud Martin; Julien Labreuche; Mouna Lazrek; Stéphanie Somers; Elodie Ribot; Sophie Alain (PLoS ONE, 2023)
Background Fecal Microbiota Transplantation (FMT) has become the preferred treatment for recurrent Clostridioides difficile Infections (CDI). However, donor screening is a complex process that varies between countries. The primary objective of screening is to prevent the transfer of potential pathogens from the donor to the recipient via feces. Many guidelines recommend Cytomegalovirus (CMV) testing as part of donor screening, but is the risk of CMV transmission well supported by evidence? Materials/methods A French prospective cross-sectional multicenter single-arm study estimated the frequency of detection of CMV in the stool of voluntary healthy donors selected for FMT. All preselected donors were tested for CMV antibodies in blood, and if positive, CMV DNA PCR was performed on whole blood and stool. For samples CMV positive in stool PCR, or case of serological markers positive for IgM, we planned isolation of CMV in cell culture. Results From June 1, 2016, to July 31, 2017, 500 healthy donors (250 per center) were recruited and 483 included. Of these, 301 were CMV seronegative, and 182 tested positive for CMV IgM and/or IgG. Stool CMV PCR was performed in 162 donors. In two cases, the initial analysis was positive, but below the limit of quantification. Repeated PCR tests using Siemens and Altostar assays were negative. No infectious CMV could be detected in cell culture of these two samples and in the stool of 6 CMV IgM-positive donors. Conclusions Our study shows that healthy volunteers with positive CMV serology do not shed CMV DNA in their stool, as detected by PCR or cell culture. This study provides another argument to remove CMV screening for FMT donors.